Complexos de cobre(II) com bases de Schiff, tipo ONNO derivados de cis- e (±)-trans-1,2-ciclohexanodiamina: síntese, caracterização e estudos como catalisadores na oxidação de catecóis - Silva, Ricardo Soares Mota (Universidade Federal de São Carlos, 2011)
Salen-type complexes are an important class of coordination compounds, which have been used to catalyze a wide variety of reactions in various homogeneous and heterogeneous systems. Complexes of transition metals are very versatile and participate in many chemical processes, which make the study of these very interesting. Research shows that the complexes of salen [salen = N, N'-ethylenebis (salicilidenoamina)] are efficient catalysts, and some compounds of this type have been investigated as catalysts in the oxidation of catechol. In this work were synthesized three types of compounds, ligands, mononuclear complexes and binuclear complexes. The three series have satisfactory yields. The compounds synthesized in this work were characterized by melting point, elemental analysis, vibrational spectroscopy in the IR region, absorption spectra in the UV-vis, conductivity measurements and solubility. The ligands were also characterized by nuclear magnetic resonance. From these characterizations, comparisons were made between ligands, mononuclear and binuclear complexes, and also with respect to the effects of the substituents on the aromatic ring taking into account series with and without methoxy substituents at positions 3, 4 and 5. The kinetics was performed using a spectrophotometer, following the formation of the product derived from oxidation of 3,5-di-tertbutylcatechol at 400 nm. It was also observed, the proportion of conversion by gas chromatography. Among the complexes that showed catalytic activity are the cis and trans complex [Cu(Cu(salcn))Cl2], kcat = 0,037 s-1 e kcat = 0,035 s-1, respectively; and the cis and trans complex [Cu(Cu(5-MeOsalcn))Cl2], kcat = 0,040 s-1 e kcat = 0,060 s-1, respectively.
Complexes of Copper (II) with Schiff bases, type ONNO derived from the cis and (±)-trans-1,2-cyclohexadiamine: Synthesis and Characterization Studies and as catalysts in the oxidation of catechols.
Keywords: Química inorgânica; Oxidação de catecóis; Cobre(II); Schiff, Bases de; CIENCIAS EXATAS E DA TERRA::QUIMICA